2018 ASEE Annual Conference &Amp; Exposition Proceedings
DOI: 10.18260/1-2--30696
|View full text |Cite
|
Sign up to set email alerts
|

Integrative Engineering Leadership Initiative for Teaching Excellence (iELITE)

Abstract: is a senior lead instructional designer at the Center for Innovation in Teaching and Learning. She collaborates with faculty to conduct research, program evaluations, and learning outcomes assessments pertinent to innovative curriculum designs and educational technologies. She is responsible for fostering continuous improvement in teaching, student experiences, and educational programs through the use of development and learning theories. Her areas of focus include, among others, experiential learning, interna… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…They often lead laboratory or recitation sessions and engage in teaching practices such as providing feedback, grading exams and assignments, and evaluating students' performance in a course. When starting their appointments, GTAs usually have yet to gain any prior teaching experience [8]. This means that the GTAs need to develop teaching competencies that allow them to design, implement, and evaluate curriculum and instruction that aims to prepare students to acquire the knowledge of a discipline and professional skills such as collaboration and communication.…”
Section: Gtas In Engineeringmentioning
confidence: 99%
See 1 more Smart Citation
“…They often lead laboratory or recitation sessions and engage in teaching practices such as providing feedback, grading exams and assignments, and evaluating students' performance in a course. When starting their appointments, GTAs usually have yet to gain any prior teaching experience [8]. This means that the GTAs need to develop teaching competencies that allow them to design, implement, and evaluate curriculum and instruction that aims to prepare students to acquire the knowledge of a discipline and professional skills such as collaboration and communication.…”
Section: Gtas In Engineeringmentioning
confidence: 99%
“…The definitions of the seven TPACK domains ( [4], p. [3][4][5][6][7][8][9][10] Pedagogical Knowledge (PK) Knowledge about the process and practices or methods of teaching and learning and how it encompasses educational purposes, values, and aims (e.g., student learning, classroom management, lesson plan development and implementation).…”
Section: Tablementioning
confidence: 99%
“…Theory-driven evaluation assesses not only whether an intervention program is effective or not (program outcomes), but also utilizes program theory to frame the evaluation. The program has achieved its intended outcomes of the program-an increase of students' teaching self-efficacy-and an outcome study has been reported 17 . As a next step, the objective of this paper is to understand how a program theory based on the program designer's assumptions are shared or not shared.…”
Section: Program Evaluationmentioning
confidence: 99%
“…11,12 While the majority of these courses focus on teaching skills within the academic realm, several courses have also emphasized skills transferable to non-academic careers such as leadership and communication. 12,13,14 In this paper, we build upon this growing body of work to document an instructional improvement project for Chemical Engineering 375, Professional Preparation: Teaching Chemical Engineering, a 2-unit course for graduate students at the University of California, Berkeley. This course is typically taken during the first semester for PhD students, and it complements a set of three technical chemical engineering courses.…”
Section: Introductionmentioning
confidence: 99%